Excellent energy storage and discharge performances in Na1/2Bi1/2TiO3-based ergodic relaxors by enlarging the [AO12] cages. Issue 22 (27th May 2022) - Li, Miaomiao; Zhu, Mankang; Zheng, Mupeng; Hou, Yudong; Wang, Jitong; Chao, Xiaolian; Yang, Zupei; Zhou, Jinling; Wang, Ke; Ke, Xiaoxing
Abstract : By introducing K0.5 Bi0.5 (Zn1/3 Nb2/3 )O3, the [AO12 ] cages are enlarged, which enhances the local polarization; meanwhile, the long-range correlations are disrupted, which renders PNRs percolate to room temperature. Finally, a high recoverable energy density of 5.1 J cm −3 and a high efficiency over 80% are obtained. Abstract : In this work, a lead-free 0.86(0.93Na1/2 Bi1/2 TiO3 -0.07BaTiO3 )-0.14K1/2 Bi1/2 (Zn1/3 Nb2/3 )O3 (KBZN14) ergodic relaxor demonstrates excellent energy storage performance: W s = 6.48 J cm −3, W r = 5.10 J cm −3, and η = 80% at a moderate field of 29.0 kV mm −1, accompanied by an outstanding frequency and temperature stability as well as a fast discharge rate t 0.9 of 69–79 ns. The excellent energy storage performance of the sample KBZN14 originates from the synergic effect of KBZN introduction: the enlargement of the [AO12 ] cages of the pseudocubic perovskite host to facilitate the local polarization, and the complex cations (Zn1/3 Nb2/3 ) 4+ destroy the long-range correlations to percolate the polar nanoregions (PNRs) to room temperature. Our work provides a way to design NBT-based materials as a candidate for high energy density and pulse capacitor applications.